Implementing and Replicating Perinatal Mental Health Programs in Portuguese Public Hospitals: Protocol of a Pilot Program - Denise Leite; Carla Santanita; Teresa Reis (Revista Portuguesa de Psiquiatria e Saúde Mental, 2024)
Introduction: Pregnancy and postpartum are periods of increased risk for the development or exacerbation of mental disorders. Preventing the impact and consequences of untreated mental illness is essential, given the risks for the woman and the baby. In Portugal, there are a limited number of programs and projects oriented towards intervention in this period of vulnerability. The perinatal mental health program whose protocol is presented was designed to integrate perinatal mental health care in a public hospital, through a pilot model approach for the detection and provision of adequate, specific and timely care. Our objective was to describe the design and methodology of a perinatal mental health program implemented in a public hospital in Portugal and reflect on its replicability within the National Health Service context.